Os Fundamentos Místicos da Ciência Baconiana - Branco, Daniel Artur Emidio (2018)
This work aims to investigate the mystical foundations of the science of Francis Bacon (1561-1625). Different works of the author will be studied, among them, Novum Organum, The Advancement of Learning, New Atlantis, Wisdom of the Ancients and Essays. The influence of mysticism over baconian thought in both esoteric and religious aspects, specifically over his idea of science, will lead to the present investigation, which also will investigate Bacon's degrees of acceptance and rejection of the ancient thinkers, especially Aristotle and Plato, his relation to modern and contemporary sciences and the meaning of his own science. Also this work will will also explore the influence of the Renaissance and the Religious Reformation over Bacon and the total dimension of his thought, which uses the inductive method, but goes beyond it. Finally, it will be discovered that Bacon's legacy is not limited to the inductive method, that it is imperative to think Bacon's work without the modern eye and it‘s necessary to study him under the paradigm of mysticism. In this way there is the knowledge of the actuality and relevance of the english philosopher to the academic world.